Impacts of small-scale irrigation water use on environmental flow of ungauged rivers in Africa - Geleta, Y.; Simane, B.; Assefa, E.; Haileslassie, Amare (Springer, 2023)
Failure in Environmental flow in quantity, timing, and quality leads to failure to support ecosystems, human livelihoods, and well-being. Irrigation water use is one of the main actors in impacting the water flow of rivers in quantity and time but was not well investigated in many ungauged catchments under smallholder irrigation systems. This study examined the impact of irrigation water use on environmental flow in Arata's small ungauged catchment. The study estimated the flow in sub-catchment using the area ratio method, the crop irrigation water requirement using F.A.O. cropwat 8.0, and the water balance in the Water Evaluation and Planning System tool and the environmental flow in Tennants, Q95, asnd local area thumb rule. The result showed that the minimum environmental flow of the Arata catchment is 290, 310, and 60 li/sec in the Tennant, Q95, and the local thumb rule. Irrigation consumes only 9% of the water resources of the catchment while 91% is contributed to downstream lake Ziway via Ketar river. January and February have unmet water demand and zero environmental flow. In December Tennant's 10% and Q95 recommended environmental flow had 19% and 24% deficit while the thumb rule environmental flow is 291% more than the minimum requirement. The rest of the months are by far more than the minimum environmental flow requirement. Given the result, meeting the environmental flow of the system throughout the year needs the installation of a water storage facility from upstream to downstream, the introduction of different water-saving irrigation technologies, farmers' capacity building in irrigation water management, and a standardized environmental flow estimation mechanism.